2020
DOI: 10.1111/lam.13276
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community succession and toxic alkaloids change during fermentation of Huafeng Dan Yaomu

Abstract: Fermentation is a traditional processing method that can impact the abundance of relevant components in Chinese herbal medicines. Huafeng Dan Yaomu was processed by fermentation. In this study, we investigated changes in toxic alkaloids using high‐performance liquid chromatography and analysed the changes in microbial communities during fermentation of Huafeng Dan Yaomu by Illumina MiSeq platform. The results indicated that highly toxic alkaloid compounds including aconitine, mesaconitine and hypaconitine were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It has been shown that glycoalkaloids can inhibit LAB growth [ 25 ] and hence compromise the fermentation process. Nevertheless, it is reported that glycoalkaloids can be metabolised during the fermentation process [ 23 , 24 ], in which some types of Lactobacillus strains, including Lactiplantibacillus plantarum , can play a key role in diminishing the potential health risk posed [ 22 , 24 ]. Thus, considering the high amounts of glycoalkaloids present in unripe green tomatoes, it is hypothesised that differences between the ability of LAB strains to grow in the presence of solanine may provide some insight regarding their ability to degrade them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that glycoalkaloids can inhibit LAB growth [ 25 ] and hence compromise the fermentation process. Nevertheless, it is reported that glycoalkaloids can be metabolised during the fermentation process [ 23 , 24 ], in which some types of Lactobacillus strains, including Lactiplantibacillus plantarum , can play a key role in diminishing the potential health risk posed [ 22 , 24 ]. Thus, considering the high amounts of glycoalkaloids present in unripe green tomatoes, it is hypothesised that differences between the ability of LAB strains to grow in the presence of solanine may provide some insight regarding their ability to degrade them.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the use of appropriate LAB strains provides an opportunity to mitigate the potential risk of high glycoalkaloid content in fermented products: some Lactobacilli spp. have been shown to reduce SGAs by up to 50% [ 22 , 23 , 24 ]. On the other hand, Friedman [ 25 ] suggests an inhibitory effect of SGAs on Lactobacilli spp., which might affect the fermentative potential of lactic strains.…”
Section: Introductionmentioning
confidence: 99%
“…Through fermentation, the levels of antinutrients, toxic substances, and digestive enzyme inhibitors, in food are substantially reduced [ 38 , 39 ]. When traditional herbal medicines are fermented with microorganisms, the toxic components in them are decomposed, and their side effects are alleviated [ 40 , 41 , 42 ]. Fermentation reduces the levels of some components in food and traditional herbs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have reported the impact of other processing methods on the fungal community. Cao et al analyzed the variation of microbial community during the fermentation of Huafeng Dan Yaomu and found that the dominant fungal genera changed from Millerozyma and Saccharomycopsis to Pichia after 14 days of fermentation ( 38 ). In Nigeria, Omohimi et al collected yam samples (including raw samples, chips, flakes, and flour) to compare the difference in fungal contamination.…”
Section: Discussionmentioning
confidence: 99%